(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
The generation of environmentally and sustainable energy is a basic need towards proffering a solution to the climatic and scientific challenges confronting twenty-first century human race. This quest has led to the discovery of diverse unconventional energy resources existing presently. Amongst all these viable options, solar energy is considered to have the best prospect in view of its all-year availability, no geographical restriction and the \(3.8 × 10^26\) Joule of energy it gives off per second. This energy can be tapped either using direct or indirect means; the use of natural dyes to mimic photosynthesis in dye-sensitized solar cell (DSC) device is a response to provide an economical and technical substitute to traditional \(p\)-\(n\) junction photovoltaic devices. DSC is a systematic device that uses disorderly technology to produce electricity in diverse light conditions such as outdoors, in poor lightning conditions. The devices are also able to convert both natural and man-made light into energy to power technology through a broad range of electronic devices. In this paper, we present almond dye-sensitized cells spectral responses with four different electrolyte sensitizers. The result is DSCs with a comparative output efficiency of 3.24%, Voc of 306 mV with KBr; the least efficient DSC was HgCl\(_2\) electrolyte sensitized with an output efficiency of 0.09% under same standard atmospheric conditions of 1.5 A.M and temperature of 27.1 \(^°\)C and pH of 5.49.